Literature Study: Leptospirosis in Dogs 2012-2021 Period - Muhammad Fahmi Al Rasyid; Ajeng Erika Prihastuti Haskito; Dodik Prasetyo; Agri Kaltaria Anisa (Universitas Airlangga, 2023)
Background: Leptospirosis is a zoonotic disease caused by Leptospira interrogans and infects almost all mammals. Purpose: Finding out the correct diagnosis and choosing the best treatment outcome regarding clinical symptom recovery and confirmatory investigations. Method: This literature study compared the percentage of related parameters from 18 cases and discussed 18 cases of dogs infected with leptospirosis with international coverage. Based on the literature, methods for diagnosing leptospirosis in dogs include anamnesis, clinical symptoms, abnormal clinical pathology findings, serological tests such as the Microscopic Agglutination Test (MAT), and molecular diagnostics such as Polymerase Chain Reaction (PCR). Results: Dominant clinical symptom in the digestive system was vomiting (55%), whereas the consistent hematological finding was thrombocytopenia (55.5%), and the consistent blood chemistry finding was elevated BUN (66.6%). Most case studies used the molecular diagnostic method MAT which found positive results (55.5%). Therapeutic management carried out in the case studies included causative treatment of antibiotics (doxycycline, benzylpenicillin, amoxicillin, and enrofloxacin), fluid therapy (crystalloids), antioxidants (vitamin C), mucolytics (N-acetylcysteine), and antiemetics (metoclopramide). The number of patients declared cured was 44.5%, and 55.5% died. Conclusion: The predominant clinical symptoms of leptospirosis are categorized as non-specific, with the largest number being vomit. The dominant method of diagnosis of leptospirosis was obtained from 16 cases using hematology and blood chemistry tests. The therapy is given causatively, namely doxycycline antibiotics, whereas symptomatic signs are resolved using metoclopramide as an antiemetic.